Effect of Cardiac Rehabilitation Program on Quality of Sleep in Patients with Coronary Artery Bypass Graft Surgery - Soheila Ranjbaran; Tahereh Dehdari; KHosro Sadeghniiat-Haghighi; Mahmood Mahmoodi Majdabadi (Zanjan University of Medical Sciences and Health Services, 2015)
800x600 Background and Objectives: Poor sleep quality is a common problem among patients with coronary artery bypass surgery. The aim of this study was to assess the effect of cardiac rehabilitation program on improving quality of sleep in patients with poor sleep quality after coronary bypass surgery. Materials and Methods: This was a quasi-experimental study. From 88 patients referred to the cardiac rehabilitation clinic of Tehran Heart Center, 50 patients with poor sleep quality were recruited to the study. patients after complete demographic and sleep quality questionnaires, participated in an 8-weeks cardiac rehabilitation program including exercise training and life style education sessions. Participants were followed-up 4 weeks after the intervention. Data were analyzed in the SPSS-18 using statistical tests such as Paired t-test, Independent samples T test, and One-way ANOVA. Results: After cardiac rehabilitation program, significant differences were shown in the sleep quality (p<0.001) and its dimensions including subjective sleep quality (p=0.024), sleep disturbances (p=0.002), using sleep medications (p<0.001), and day time dysfunction (p<0.001). Conclusion: The findings showed that cardiac rehabilitation programs had positive effect on improving quality of sleep in patients after coronary artery bypass surgery. Normal 0 false false false EN-US X-NONE FA /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal" mso-tstyle-rowband-size:0 mso-tstyle-colband-size:0 mso-style-noshow:yes mso-style-priority:99 mso-style-parent:"" mso-padding-alt:0cm 5.4pt 0cm 5.4pt mso-para-margin:0cm mso-para-margin-bottom:.0001pt mso-pagination:widow-orphan font-size:10.0pt font-family:"Calibri","sans-serif" mso-bidi-font-family:Arial}